Sludge-derived biochars: A review on the influence of synthesis conditions on pollutants removal efficiency from wastewaters. (July 2021) - Jellali, Salah; Khiari, Besma; Usman, Muhammad; Hamdi, Helmi; Charabi, Yassine; Jeguirim, Mejdi
Abstract: Pyrolysis is a thermochemical process that permits the conversion of biomasses into energy (bio-oil and biogas) and a solid residue called biochar. The generation of biochar from lignocellulosic materials has been, for longtime, the predominant research focus. Wastewater treatment plants produce huge amounts of sludge biomass and there exists an increasing evidence for their possible reuse as a promising pyrolysis feedstock in recent literature. Though the valorization of biochars generated from lignocellulosic biomasses has been the subject of many reviews, there exists a critical knowledge gap regarding the effect of synthesis conditions of the sludge-derived biochars (SDBs) on their efficiency in the treatment of wastewater. This review critically analyzes the available literature related to SDBs characteristics and application to adsorb inorganic and organic pollutants from effluents. The physico-chemical properties and adsorption efficiency of SDBs are mainly tuned by the nature of raw sludge, pyrolysis conditions, and pre/post-treatments. Indeed, biochars originating from digested sludge have better adsorption capacities towards nutrients and heavy metals compared to those obtained from the non-digested sludge. The nutrients recovery from urban wastewater could be significantly improved when the raw sludge is mixed with lignocellulosic biomass and Mg/Ca rich materials. On the other hand, the chemical activation of sludge at reagent/sludge ratios higher than 2:1 permits to generate SDBs with adsorption capacities comparable and even better than commercial activated carbons. Moreover, the embedment/coating of SDBs with specific nanomaterials and tailored functional groups could significantly improve the adsorption capacities of various organic toxic pollutants and at the same time enhance their chemical degradation. The effect of the nature of target pollutants (organic or inorganic) on the underlying adsorption mechanisms by SDBs was also deeply reviewed. Finally, this paper provides the main application challenges as well as insights regarding the promising future directions for SDBs research and development. Highlights: This review evaluates the use of sludge-derived biochars for wastewater treatment. Synthesis conditions influence the adsorption properties of SDBs. Higher removal capacities of pollutants are obtained with activated SDBs. Significant increases of removal capacities with nanocomposite-embedded SDBs. Adsorption mechanisms are different for organic and inorganic pollutants.